2017
DOI: 10.3389/fphar.2017.00243
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Adenosine Receptors for the Treatment of Cardiac Fibrosis

Abstract: Adenosine is a ubiquitous molecule with key regulatory and cytoprotective mechanisms at times of metabolic imbalance in the body. Among a plethora of physiological actions, adenosine has an important role in attenuating ischaemia-reperfusion injury and modulating the ensuing fibrosis and tissue remodeling following myocardial damage. Adenosine exerts these actions through interaction with four adenosine G protein-coupled receptors expressed in the heart. The adenosine A2B receptor (A2BAR) is the most abundant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 75 publications
(95 reference statements)
0
49
0
Order By: Relevance
“…Likewise, bradykinin receptors, Gi-coupled BR1, and Gq-coupled BR2 have been shown to be expressed in cardiac myofibroblasts [99,100]. In addition, purinergic signaling has also been shown to play an important role in cardiac fibrosis [101,102]. For the P1 receptors (adenosine receptors), RT-PCR has shown that mRNAs for all four P1 receptor subtypes, A 1 AR, A 2A AR, A 2B AR, and A 3 AR, are expressed in rat cardiac fibroblasts, with A 2B ARs being the most abundant [102].…”
Section: Signaling Pathways Mediating Ca 2+ Release In Cardiac Fibrobmentioning
confidence: 99%
“…Likewise, bradykinin receptors, Gi-coupled BR1, and Gq-coupled BR2 have been shown to be expressed in cardiac myofibroblasts [99,100]. In addition, purinergic signaling has also been shown to play an important role in cardiac fibrosis [101,102]. For the P1 receptors (adenosine receptors), RT-PCR has shown that mRNAs for all four P1 receptor subtypes, A 1 AR, A 2A AR, A 2B AR, and A 3 AR, are expressed in rat cardiac fibroblasts, with A 2B ARs being the most abundant [102].…”
Section: Signaling Pathways Mediating Ca 2+ Release In Cardiac Fibrobmentioning
confidence: 99%
“…Recently, adenosine and its analogs have emerged as potential therapeutic agents for treatment of numerous conditions from cancers to inflammatory diseases (Bahreyni, Samani, Khazaei, et al, ; Bahreyni et al, ). Consistently, there are several studies showing that both A2a and A2b ADORs are expressed in cardiovascular tissues and modulation of these receptors by adenosine or pharmacological molecules plays key roles in the regulation of heart rate, blood pressure, and heart rate variability in the cardiovascular system (Thomas et al, ; Vecchio, White, & May, ). As summarized in this review, although it is admitted that A2 ADOR subtypes have regulatory effects on the cardiovascular system and dysfunction of these receptors triggers CVD, the exact role of adenosine and its analogs in pathogenesis of CVD is quite controversial; therefore, further investigations are required to clarify the precise role of adenosine and A2 ADOR in the cardiovascular system.…”
Section: Resultsmentioning
confidence: 61%
“…In contrast, in the skin, liver, and lungs, adenosine A2A and A2B receptors both mediate an increase in fibrosis. It is also striking that different adenosine receptors appear to play a dominant role in fibrosis in different organs; adenosine A2A receptors are the dominant receptors in the skin, peritoneum, and liver but A2B receptors are responsible for pulmonary fibrosis (Bruce et al, 2011 andVecchio et al, 2017).…”
Section: Ibuprofenmentioning
confidence: 99%